An Analysis of the Equivalence in Translating English Idioms into Indonesian at the English Education Department - Hafiza, Khairia; Anastasia, Faurina; Siregar, M. Riskiyadi (English Tadris Department, Tarbiyah and Teacher Training Faculty, Datokarama State Islamic University Palu, 2025)
This research aims to analyze the use of equivalence in translating English idioms into Indonesian by students of the English Education Department at State Islamic University of Sultan Syarif Kasim Riau. The study employed a quantitative descriptive method. This research applied the Stratified Random Sampling technique. The test was the main intrument of the research. The data were collected from students’ translation of 20 sentences containing idiomatic expressions and analyzed using Nida and Taber’s theory of equivalence, which classifies translation into dynamic and formal equivalence. The findings revealed that most students tended to use dynamic equivalence more frequently than formal equivalence. Out of 480 total translation products, 45.4% were categorized as dynamic equivalence, 37.3% as formal equivalence, 13.5% as non-equivalent, and 3.8% were left untranslated. Although many translations successfully conveyed the intended idiomatic meaning, some failed due to literal translation or lack of contextual understanding. This research is expected to contribute to translation studies, particularly in improving students’ competence in translating idiomatic expressions meaningfully and accurately.